Polarization multiplexing multichannel high-Q terahertz sensing system - Wang, Xiuyu; Wang, Xiaoman; Ren, Qun; Cai, Haocheng; Xin, Jihong; Lang, Yuxin; Xiao, Xiaofei; Lan, Zhihao; You, Jian Wei; Sha, Wei E. I. (Frontiers in Nanotechnology, 2023)
Terahertz functional devices with high Q factor play an important role in spectral sensing, security imaging, and wireless communication. The reported high-Q terahertz devices based on the EIT effect can not meet the actual needs of applications. Quasi-BIC does not meet the condition of orthogonality of resonance state, so that it can be excited by the incident wave, and the quality factor is greatly improved. The split ring resonator (SRR) is one of the most representative artificial microstructures on the metasurface, and it shows great potential in BIC. In this paper, based on the classical SRR structure, we combine the large and small SRRs and change the resonance mode of the inner and outer SRRs by changing the radius of the inner SRR. The metasurface based on Friedrich-Wintgen BIC verified that the continuous modulation of parameters in a system could make a pair of resonant states strongly coupled, and the coherent cancellation of the resonant states will cause the linewidth of one of the resonant states to disappear, thus forming BIC. Compared with the single SRR metasurface based on symmetrical protection BIC, the dual SRR surface designed in this paper based on accidental FW-BIC has multiple FW-BIC states, which realizes polarization multiplexing multichannel. It provides a brilliant platform for high-sensitivity optical sensor array, low threshold laser and efficient optical harmonic generation.